2019
DOI: 10.3390/su11164298
|View full text |Cite
|
Sign up to set email alerts
|

Forage Fish as Food: Consumer Perceptions on Baltic Herring

Abstract: Using fish resources for food supply in a sustainable and efficient way requires an examination of the feasibility of prioritising the use of forage species. The present paper deals with the issue from the consumer perspective. Using Baltic herring as a case study, the role of sociodemographic determinants, the drivers and barriers of Baltic herring consumption are investigated in four Baltic Sea countries, based on an internet survey. The drivers and barriers of Baltic herring consumption are compared to thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In addition, the consumption of Baltic herring has been decreasing during the last decades and is now less than a kilogram per year, varying between age groups (older people tend to eat more), genders (males tend to eat more) and countries (Estonians tend to eat more and Danes less than the three other countries studied). People reported that better availability of easy-to-prepare products, interesting recipes, and reduced pollutant levels would increase their consumption of Baltic herring [11]. In contrast, recommendations to reduce consumption on average would have little effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the consumption of Baltic herring has been decreasing during the last decades and is now less than a kilogram per year, varying between age groups (older people tend to eat more), genders (males tend to eat more) and countries (Estonians tend to eat more and Danes less than the three other countries studied). People reported that better availability of easy-to-prepare products, interesting recipes, and reduced pollutant levels would increase their consumption of Baltic herring [11]. In contrast, recommendations to reduce consumption on average would have little effect.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was designed and conducted for the purposes of this study and another study investigating consumers' perception and consumption of fish. The latter study [11] was published first, and it contains a more detailed description of the study methods, including the questionnaire.…”
Section: Consumption Surveymentioning
confidence: 99%
“…Also Baltic herring consumption has been decreasing during the last decades and is now less than a kilogram per year, varying between age groups (old people eat more), genders (males eat more) and countries (Estonians eat more and Danes less than other countries studied). People reported that better availability of easy products, recipes, and reduced pollutant levels would increase their Baltic herring consumption [11] . In contrast, recommendations to reduce consumption would have little effect on average.…”
Section: Discussionmentioning
confidence: 99%
“…Third, Baltic herring has also other important values than health: economic (Baltic herring is the most abundant catch species by weight in the Baltic Sea), ecological (sustainable yield of Baltic herring is large and the catch removes nutrients from the sea), climate (Baltic herring could replace red meat and other climate-unfriendly food sources), social (Baltic herring is inexpensive local food), and cultural (Baltic herring and salmon are an important part of coastal culture) [60] [61] . Moreover, Baltic herring has value for food security [62][5] [11] . Should these values be considered when dioxin policy is designed?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation